Analysis of Elementary School Students' Ability in Solving Geometry Problems Minimum Competency Assessmen - Muhammad Rijal Wahid Muharram; Desi Ratna Sari; Epon Nur’aeni Lukman (LPPM Universitas Buana Perjungan Karawang, 2021)
Implementation of the Minimum Competency Assessment (AKM) which will be held at the school education level, especially at the elementary school education level requires preparation in order to carry it out. One of the components that must be prepared are students. The readiness of the student aspect in this case is seen as very important because it is a subject that will be tested in the implementation of the Minimum Competency Assessment (AKM). The basic competencies that are tested on students are divided into 2 competencies, namely reading literacy and numeracy. One of the scopes of the material in the Numeration AKM that is tested is geometry. This study discusses the analysis of the ability of elementary school students in solving geometry problems in the Minimum Numeration Competency Assessment. This study aims to see and describe the ability of fourth grade students in solving geometry problems in the AKM Numeration in terms of the quality of student responses based on the results of students' completeness in completing the test. This study uses a qualitative description method. The data were obtained from the results of tests and interviews with fourth grade students in the neighborhood of RT 04 Pasirjaya, Tasikmalaya City. There is 1 grade IV student who is the subject of this research. The results of this study indicate that the student's ability to solve geometry problems in the Minimum Numeration Competency Assessment is relatively low, with a percentage of 17.65%.